2016
DOI: 10.7196/samj.2016.v106i6.10335
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic and incidental HPV types associated with histologically confirmed cervical intraepithelial neoplasia in HIV-positive and HIV-negative South African women

Abstract: In South Africa, burdened by the HIV pandemic, high numbers of high- and low-risk HPV type infections are present in women with cervical preneoplasia. HPV type distribution differs among varying levels of HIV-induced immune depletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
3
10
1
Order By: Relevance
“…Similar to earlier studies we found WLWH to be significantly more prone to have multiple HR HPV infections than HNW [167][168][169] . The clinical significance of multiple infections is unclear as prospective evidence on this issue is limited 170 .…”
Section: Regarding Hpv Genotypes Associated With High-grade Cervical supporting
confidence: 91%
“…Similar to earlier studies we found WLWH to be significantly more prone to have multiple HR HPV infections than HNW [167][168][169] . The clinical significance of multiple infections is unclear as prospective evidence on this issue is limited 170 .…”
Section: Regarding Hpv Genotypes Associated With High-grade Cervical supporting
confidence: 91%
“…[ 17 , 18 ] However, many previous studies used only cytology results synonymously with cervical premalignant changes and none of them correlated with absolute CD4 count and CD4 percentage, concurrently. [ 19 21 ] Because cytology is only a screening test, it is important that the oncogenic HPV genotypes be confirmed inside the tumor itself. [ 15 ] Lack of characterization of age, absolute CD4 count and CD4 percentage concurrently in women with cervical disease, makes the association of diagnostic clinical immune parameters in women with cervical disease unclear, particularly in HIV-1 infected women in South Africa, where HIV-1 prevalence and incidence in women are among the highest in the world.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HPV in HIV-infected patients is higher than in non-HIV-infected individuals and varies over time and with the degree of immunosuppression. In people with immunosuppression, warts may become extensive, may frequently relapse after treatment, and are more likely to be dysplastic [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%